2014
DOI: 10.1007/s11224-014-0485-4
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the N → Sn coordination in (Me3SnCN)2

Abstract: The N → Sn coordination occurring in the (Me 3 SnCN) 2 dimer has been investigated using various computational methods and several theoretical tools possessing great interpretative potential. The dimer is formed by moving the C≡N fragment of the first Me 3 SnCN molecule close to the Sn atom of the second molecule and the resulting N → Sn coordination corresponds to that observed in the crystal structure of trimethyltin cyanide. The geometry of (Me 3 SnCN) 2 is optimized using the MP2 method and its 11 variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 93 publications
3
24
0
Order By: Relevance
“…Fifth, the spin-component scaled variant of MP2 demonstrates poor accuracy in the calculated DE value for the cc-1b, which results in the wrong ordering of the cc-and tt-conformers. On the other hand, SCS-MP2 shows an improvement in DE for 1a over MP2, which in turn is in line with previous reports on the improved performance of SCS-MP2 in providing the structural and energetic description of conformations for molecules [50,51] and molecular complexes [52][53][54].…”
Section: Relative Energiessupporting
confidence: 91%
“…Fifth, the spin-component scaled variant of MP2 demonstrates poor accuracy in the calculated DE value for the cc-1b, which results in the wrong ordering of the cc-and tt-conformers. On the other hand, SCS-MP2 shows an improvement in DE for 1a over MP2, which in turn is in line with previous reports on the improved performance of SCS-MP2 in providing the structural and energetic description of conformations for molecules [50,51] and molecular complexes [52][53][54].…”
Section: Relative Energiessupporting
confidence: 91%
“…[25,26,38,98,99] Previous studies have confirmed the trend that the tetrel bond grows stronger as T becomes larger, [30,32,33,47,100] but that the effect levels off between Sn and Pb. However, there are a few works dealing with tetravalent Sn and Pb, and the noncovalent bonds they form with various bases.…”
Section: Discussionmentioning
confidence: 82%
“…Closely related to these interactions are those in which the bridging atom comes from the tetrel family (C, Si, Ge, etc). [16][17][18][19][20][21] There is a rapidly growing literature [22][23][24][25][26][27] that has provided a wealth of insights into the chemical and physical phenomena that underlie tetrel bonds. This larger number of substituents obstructs a clear passage of an approaching nucleophile toward the tetrel atom, [8] which can inhibit the formation of such a bond or at the least require a good deal of deformation so as to clear a space for the Lewis base.…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by ε elst in Table , the interaction between SnX n and py is determined to a great extent by electrostatic forces, providing at least 41.8% of the total attraction. The importance of electrostatics in N → Sn is supported by the results of our previous study of (Me 3 SnCN) 2 . The SAPT analysis of N → Sn coordination linking two Me 3 SnCN molecules proved that these molecules were held together mainly by electrostatic interactions.…”
Section: Resultsmentioning
confidence: 86%